Upaya Mengatasi Hipertensi dalam Kehamilan di Pelayanan KIA Puskesmas Grogol Petamburan (Kajian di Puskesmas Grogol Petamburan) - Tiarma Talenta Theresia; Sri Lestari; Susilo Widyanto; Budiman Budiman; Bilqis Ghina Tsamarah; Jesslyne Angellique; Priscilla Olivia Akwila Effendy; Rachel Victoria Williem; Syifa Luthfiyah; Theresia Christy Vinsensius (Universitas Respati Indonesia, 2025)
Hypertension in pregnancy is one of the leading causes of maternal and neonatal morbidity and mortality. In the working area of Grogol Petamburan Public Health Center, the incidence of hypertension among pregnant women continues to rise annually, contributing to a high rate of pregnancy complications. This study aims to reduce complications associated with hypertension in pregnancy through the SI-PERI MALAM innovation using the 5 PERI CETAR SEHATI strategy, which integrates early detection, health education, family support, non-pharmacological therapy, and guided physical activity. This descriptive observational study applied a pre–post test design without a control group involving 12 hypertensive pregnant women. The 14-day intervention was carried out through five stages: Si-Peri Gece (blood pressure monitoring), Si-Peri Pintar (education via digital pocketbook and maternal classes), Si-Peri Siaga (family support), Si-Peri Sehat (daily cucumber juice consumption), and Si-Peri Aktif (prenatal yoga). The results showed a significant decrease in blood pressure among all participants, improved maternal knowledge, and a reduction in both maternal and neonatal complications. This program proved effective in improving the health status of hypertensive pregnant women through a holistic approach and holds potential as a national model for managing hypertension during pregnancy.